Cutting their cloth: the Scottish Premonstratensians, c. 1150 to c. 1350 - Oram, Richard (Places of worship in Britain and Ireland, 1150-1350, 2018)
Keywords: 🇬🇧 great britain (general)

The Premonstratensian Canons - Smith, David M. (The Heads of Religious Houses: England and Wales, III. 1377–1540, 2008)
All the houses were abbeys except where specifically stated otherwise.ALNWICK (Northumberland), St Mary f. 1147 x 1148Lists in Colvin, pp. 392–3; A. M. Oliver in Proc. Soc. Ant. Newcastle, 3rd ser., IX (1919–20), 42–4; Heads, I, 192; Heads, II, 491.Walter de Hepscott (Hepescotes) Occ. 15 Aug. 1376 (Ch. Alnwick, p. 43).John Frechevyl Occ. 1379 (TNA, E179/62/4, m. Id).William (de) Rok (Rokk') Occ. 6 Feb. 1395 (DCM, Reg. II, f. 315v); Trin. 1404 (called Kok), Hil. 1407 (Dendy, Arch. Aeliana, 3rd ser., 6 (1910), 67–8); 10 Apr. 1407 (Nbld and Durham Deeds, p. 156).John Occ. [1415] (TNA, E101/214/5B, m. 21).John Cudberde 1419– Can. of Alnwick, pres. of abb.-el. for bl., no reason being given for the vacancy 12 May 1419 (Reg. Langley, V, p. 115, no. 1414). Probably to be identified with the abb. John who occ. from 20 June 1421 (ibid., V, p. 153, no. 1478) to 8 March 1435 (ibid., IV, p. 152, no. 1144).William Marschal (Marschall) 1437– Can. of Alnwick, pres. of abb.-el. for bl., no reason being given for the vacancy 25 May 1437 (ibid., V, p. 34, no. 1293); commn to bl. 4 July 1437 (ibid., p. 35, no. 1294). He was previously vicar of Chatton (ibid., p. 36, no. 1295). Is he the same as William below?
Keywords: 🇬🇧 great britain (general)

A la recherche d'un environnement accueillant: les Prémontrés dans les circaries d'Écosse, d'Angleterre, de Flandre et de Brabant - Appelmans, Janick (Actes officiels des 26e et 27e colloques du Centre d'Etudes et de Recherches Prémontrées, Saint-Brieuc - Abbaye de Beauport, 2000 [et] Arras -Prémontré, 2001, 2002)
Keywords: 🇧🇪 belgium (general); 🇬🇧 great britain (general)

The Provincial and General Chapters of the English Premonstratensians and their Acta, 1459-1504 - Gribbin, Joseph A. ("Stand up to godwards" : essays in mystical and monastic theology in honour of the reverend John Clark on his sixty-fifth birthday, 2002)
Keywords: ⚖️ chapters and statutes; 🇬🇧 great britain (general)

The Premonstratensian Canons - Smith, David M.; London, Vera C. M. (The Heads of Religious Houses: England and Wales, II. 1216–1377, 2001)
Keywords: 🇬🇧 great britain (general)

The Premonstratensian Order in Late Medieval England - Gribbin, Joseph A. (Studies in the History of Medieval Religion, 2000)
Keywords: 🇬🇧 great britain (general)

The Libraries of the Cistercians, Gilbertines, and Premonstratensians - Bell, David N. (Corpus of British medieval library catalogues, 1992)
Keywords: 🇬🇧 great britain (general)

Le décret ordonnant la participation des Abbés anglais au Chapitre Général de Prémontré fut-il promulgué en 1182? - Gerits, Trudo (Analecta Praemonstratensia, 1966)
Keywords: ⚖️ chapters and statutes; 🇬🇧 great britain (general)

Monasteria Angliae, saeculo decimo sexto - Valvekens, Johannes B. (Analecta Praemonstratensia, 1965)
Keywords: 🇬🇧 great britain (general)

A propos de l'organisation des bibliothèques médiévales de l'Ordre de Prémontré en Angleterre et en Allemagne - Gerits, Trudo (Analecta Praemonstratensia, 1961)
Keywords: 🇩🇪 germany (general); 🇬🇧 great britain (general)

The Premonstratensian Order in Scotland - Backmund, Norbert (The Innes Review, 1953)
Keywords: 🇬🇧 great britain (general)

The White Canons in England - Colvin, H.M. (Clarendon Press, 1951)
The history of the Premonstratensian order.
Keywords: 🇬🇧 great britain (general)

English masters and students in Paris during the XIIth century - Gabriel, Astrik Ladislas (Analecta Praemonstratensia, 1949)
Keywords: 🇬🇧 great britain (general); 📚 premonstratensian (general)

The white canons of St. Norbert, a history of the Premonstratensian order in the British isles and America, - Kirkfleet, Cornelius James (St. Norbert Abbey, 1943)
The Order of Canons Regular of Prémontré, also known as the Premonstratensians, the Norbertines and, in Britain and Ireland, as the White Canons (from the colour of their habit), are a religious order of Canons regular of the Catholic Church founded in Prémontré near Laon in 1120 by Norbert of Xanten, who later became Archbishop of Magdeburg. Premonstratensians are designated by O.Praem. (Ordo Praemonstratensis) following their name. Norbert was a friend of Bernard of Clairvaux and so was largely influenced by the Cistercian ideals as to both the manner of life and the government of his order. As the Premonstratensians are not monks but Canons Regular, their work often involves preaching and the exercising of pastoral ministry; they frequently serve in parishes close to their abbeys or priories.
Keywords: 🇬🇧 great britain (general); 📚 premonstratensian (general)

The Appropriated Churches of the English White Canons - Beck, Egerton (Analecta Praemonstratensia, 1930)
Keywords: 🇬🇧 great britain (general)

The Appropriated Churches of the English White Canons - Beck, Egerton (Analecta Praemonstratensia, 1929)
Keywords: 🇬🇧 great britain (general)

The Architecture of the Premonstratensians, with special reference to their Buildings in England - Clapham, A.W. (Archaeologia: or Miscellaneous Tracts Relating to Antiquity, 1923)
Keywords: 🇬🇧 great britain (general)

Collectanea anglo-praemonstratensia, documents drawn from the original register of the order and the transcript of another register - Gasquet, Francis Aidan (The Royal historical Society, 1904)
Keywords: 🇬🇧 great britain (general)

The English Premonstratensians - Gasquet, F.A. (Transactions of the Royal Historical Society, 1903)
Keywords: 🇬🇧 great britain (general)

A Sketch of the Premonstratensian Order and its houses in Great Britain and Ireland - Geudens, F.M. (Burns and Oates, 1878)
Keywords: 🇬🇧 great britain (general); 🇮🇪 ireland (general)